Comparative Evaluation of Clinical and Radiographic Changes Following Delayed Implant Placement in Mandibular Posterior Region with or without i-PRF Activation: A Split Mouth Clinical Study - Shivam Singh; Yasir S. Khan; Amitabh Srivastava; Vivek Srivastava; Ajita Meenawat; Tanu Sahney (Journal of Pharmacy and Bioallied Sciences)
Background: Injectable platelet-rich fibrin (i-PRF) is prepared without anticoagulants having improved features such as increased fibroblast migration, proliferation, and tissue angiogenesis acceleration. When administered to titanium implants, i-PRF clings to the metal surface, generating a protein coating that impacts cellular activity required for osseointegration which aids in optimum and rapid osseointegration. The present study compared and evaluated the osteogenic properties of i-PRF in dental implant sites to determine the positive impact of i-PRF on osseointegration. Methods: A split-mouth clinical study design was used, involving ten participants with twenty sites of bilaterally missing mandibular molars. The subjects were divided into two equal treatment groups (N = 10): control group, where dental implants were placed without i-PRF activation, and test group, where i-PRF-activated dental implants were placed. Results: Both groups showed similar trends in plaque index and sulcular bleeding index. However, the test group exhibited significantly higher Implant Stability Quotient scores, indicating better stability. Peri-implant probing depth showed no significant difference between groups, but the test group had lower increase in probing depth. In addition, the test group showed superior wound healing and lower crestal bone loss changes compared to the control group. Conclusions: The findings of this study contributed to understand the effectiveness of i-PRF in enhancing osseointegration in dental implants, potentially improving clinical outcomes in implant dentistry.